2007
DOI: 10.2146/ajhp070246
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic therapy: Cost efficiency and reimbursement

Abstract: Initiating a blood management program requires planning and support from those who are concerned about blood usage reduction and outcomes improvement. Launching a vigorous and ongoing educational program to raise awareness about the risks and hazards associated with blood transfusion is an important step in helping to reshape the medical staffs' attitudes about transfusion and the most cost-effective way to achieve clinical goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…We aim to build and validate a reliable statistical model for blood banking that would have a highly significant impact in improving quality, safety, access to care, and cost of care. Measures to increase efficiency and cost-effectiveness in health care are becoming increasingly important ( 7 , 8 ), and an accurate predictive algorithm for blood product usage could greatly contribute to value-based care in transfusion medicine.…”
mentioning
confidence: 99%
“…We aim to build and validate a reliable statistical model for blood banking that would have a highly significant impact in improving quality, safety, access to care, and cost of care. Measures to increase efficiency and cost-effectiveness in health care are becoming increasingly important ( 7 , 8 ), and an accurate predictive algorithm for blood product usage could greatly contribute to value-based care in transfusion medicine.…”
mentioning
confidence: 99%
“…In a prospective analysis of nearly 300 men undergoing radical retropubic prostatectomy, subjects received 600 units/kg of rHuEPO 1 and 2 weeks prior to the procedure. 18 Outcomes revealed that more than 90% of participants in the treatment group did not require allogenic blood transfusion. Furthermore, men who did require allogenic transfusion typically needed only 1 to 2 units, a substantial decrease from the half dozen units normally required for the procedure.…”
Section: Pharmacoeconomicsmentioning
confidence: 99%
“…However, a retrospective parallelgroup review of oncology and predialysis CKD (pCKD) inpatients examined the cost-effectiveness of darbepoetin alfa and rHuEPO. 18 The analysis compared an aggregate administered dose of the two ESAs. Recombinant human erythropoietin offered a cost reduction of nearly 50% when compared to darbepoetin ($755 vs $1127 oncology patients, P < .0001; $479 vs $723 pCKD patients, P < .0001).…”
Section: Pharmacoeconomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proponents often cite improved patient outcomes, reduced risk of infection, and cost savings as three legitimate benefits to implementing a blood management program (Society for the Advancement of Blood Management, 2008). Depending on the demographics of the patient population, anemia can be present in as many as 50% of surgical patients (Jaspan, 2007). A number of the processes and techniques discussed in the research address the potential benefits of blood management to anemic patients.…”
Section: Introductionmentioning
confidence: 99%